NETest liquid biopsy is diagnostic of small intestine and pancreatic neuroendocrine tumors and correlates with imaging. Issue 4 (April 2019) - Malczewska, Anna; Witkowska, Magdalena; Makulik, Karolina; Bocian, Agnes; Walter, Agata; Pilch-Kowalczyk, Joanna; Zajęcki, Wojciech; Bodei, Lisa; Oberg, Kjell; Kos-Kudła, Beata
Abstract : Introduction: Current monoanalyte biomarkers are ineffective in gastroenteropancreatic neuroendocrine tumors (GEP-NETs). NETest, a novel multianalyte signature, provides molecular information relevant to disease biology. Aim(s): Independently validate NETest to diagnose GEP-NETs and identify progression in a tertiary referral center. Materials and methods: Cohorts are 67 pancreatic NETs (PNETs), 44 small intestine NETs (SINETs) and 63 controls. Well-differentiated (WD) PNETs, n  = 62, SINETs, all ( n  = 44). Disease extent assessment at blood draw: anatomical ( n  = 110) CT ( n  = 106), MRI ( n  = 7) and/or functional 68 Ga-SSA-PET/CT ( n  = 69) or 18 F-FDG-PET/CT ( n  = 8). Image-positive disease (IPD) was defined as either CT/MRI or 68 Ga-SSA-PET/CT/ 18 F-FDG-PET/CT-positive. Both CT/MRI and 68 Ga-SSA-PET/CT negative diagnosis in WD-NETs was considered image-negative disease (IND). NETest (normal: 20): PCR (spotted plates). Data: mean ± SD. Results: Diagnosis: NETest was significantly increased in NETs ( n  = 111; 26 ± 21) vs controls (8 ± 4, p  < 0.0001). Seventy-five (42 PNET, 33 SINET) were image positive. Eleven (8 PNET, 3 SINET; all WD) were IND. In IPD, NETest was significantly higher (36 ± 22) vs IND (8 ± 7, P  < 0.0001). NETest accuracy, sensitivity and specificity are 97, 99 and 95%, respectively Concordance with imaging: NETest was 92% (101/110) concordant with anatomical imaging, 94% (65/69) with 68 Ga-SSA-PET/CT and 96% (65/68) dual modality (CT/MRI and 68 Ga-SSA-PET/CT). In 70 CT/MRI positive, NETest was elevated in all (37 ± 22). In 40 CT/MRI negative, NETest was normal (11 ± 10) in 31. In 56 68 Ga-SSA-PET/CT positive, NETest was elevated (36 ± 22) in 55. In 13 68 Ga-SSA-PET/CT negative, NETest was normal (9 ± 8) in ten. Disease status: NETest was significantly higher in progressive (61 ± 26; n  = 11) vs stable disease (29 ± 14; n = 64; P  < 0.0001) (RECIST 1.1). Conclusion: NETest is an effective diagnostic for PNETs and SINETs. Elevated NETest is as effective as imaging in diagnosis and accurately identifies progression.